2020
DOI: 10.1111/jbfa.12438
|View full text |Cite
|
Sign up to set email alerts
|

Accounting conservatism and the profitability of corporate insiders

Abstract: We predict that accounting conservatism influences insiders' opportunities to speculate on good and bad news, and thus, insider trading profitability. We find that greater conditional (unconditional) conservatism is associated with lower (higher) insiders' profitability from sales. We find limited evidence that conservatism influences profitability from purchases. These findings are consistent with our hypotheses on the different informational roles of conditional and unconditional conservatism, and on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 124 publications
1
10
0
1
Order By: Relevance
“…For instance, Chang et al (2013) argued that AC might hamper innovation performance, and managers might make less risky decisions due to market pressure. The studies also classified accounting conservatism into conditional and unconditional conservatism and discussed features of both (Khalilov and Osma 2020). In addition to these quantitative studies, several qualitative studies (Glover and Lin 2018) have also been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Chang et al (2013) argued that AC might hamper innovation performance, and managers might make less risky decisions due to market pressure. The studies also classified accounting conservatism into conditional and unconditional conservatism and discussed features of both (Khalilov and Osma 2020). In addition to these quantitative studies, several qualitative studies (Glover and Lin 2018) have also been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternate proxy for earnings quality, we use Khan and Watts's (2009) firm-year measure of earnings conservatism, C-SCORE, which is based on the timely recognition of negative events in the firms' accounts. We adopt C-SCORE as a proxy for firms' information environment to the extent that numerous authors (e.g., LaFond and Watts, 2008;Francis et al, 2013;Khalilov and Osma, 2020;Lara et al, 2020) have shown that earnings conservatism is negatively related to information asymmetry. According to Francis et al (2013), accounting conservatism is a governance mechanism that reduces information asymmetry, thus mitigating agency costs (Zaher, Mohamed, and Basuony, 2020).…”
Section: Earnings Quality Measures: Discretionary Accruals and Accounting Conservatismmentioning
confidence: 99%
“…For this analysis, we use two proxies for earnings quality 14 : (i) signed discretionary accruals based on the performance and growth, ROA&SGadjusted model (as proposed by Collins et al, 2017), and (ii) Khan and Watts's (2009) firm-year accounting conservatism measure, C-SCORE. Measures of discretionary accruals and accounting conservatism have been using in the literature as proxies for financial reporting quality (e.g., Leuz et al, 2003;Ball and Shivakumar, 2005;Hutton, Marcus, and Tehranian, 2009;Francis et al, 2013;Khalilov and Osma, 2020;Lara et al, 2020;Zaher et al, 2020). Higher (lower) values of discretionary accruals (accounting conservatism) are associated with poorer quality of the firms' financial information.…”
Section: Does the Quality Of Firms' Earnings Moderate The Impact Of Regulation On Stock Based Acquisition Returns?mentioning
confidence: 99%
“…Similarly, even though Agrawal and Cooper (2015) find weak evidence that top managers of firms misstating earnings sell more stock during the period of the misstatement, their evidence is strong when they classify insider sales on the severity of the misstatement. Firm accounting choices, like conditional conservatism (Khalilov & Osma, 2020) and accruals (Sawicki & Shreshtha, 2014), are also related to insider trades.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…Similarly, in their survey of CFOs, Graham, Harvey, and Rajgopal (2005) find that managers delay bad news in the hope they may never have to disclose it if the firm's status improves. Recognizing that conditional conservatism is a mechanism for incorporating bad news early, Khalilov and Osma (2020) show that profitability of insider sales is lower in firms with higher levels of conditional conservatism. Unconditional conservatism, on the other hand, is associated with greater profitability from insider sales.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%